Mutation of a lepidopteran‐specific PMP‐like protein, BmLSPMP‐like, induces a stick body shape in silkworm, Bombyx mori. Issue 12 (16th September 2022) - Tan, Duan; Hu, Hai; Tong, Xiaoling; Han, Minjin; Gai, Tingting; Lou, Jinghou; Yan, Zhengwen; Xiong, Gao; Lu, Cheng; Dai, Fangyin
Abstract: BACKGROUND: Lepidoptera is one of the largest orders of insects, some of which are major pests of crops and forests. The cuticles of lepidopteran pests play important roles in defense against insecticides and pathogens, and are indispensable for constructing and maintaining extracellular structures and locomotion during their life cycle. Lepidopteran‐specific cuticular proteins could be potential targets for lepidopteran pest control. But information on this is limited. Our research aimed to screen the lepidopteran‐specific cuticular proteins using the lepidopteran model, the silkworm, to explore the molecular mechanism underlying the involvement of cuticular proteins in body shape construction. RESULTS: Positional cloning showed that BmLSPMP‐like, a gene encoding a lepidopteran‐specific peritrophic matrix protein (PMP) like protein which includes a peritrophin A‐type chitin‐binding domain (CBM_14), is responsible for the stick ( sk ) mutation. BmLSPMP‐like is an evolutionarily conserved gene that exhibits synteny in Lepidoptera and underwent purifying selection during evolution. Expression profiles demonstrated that BmLSPMP‐like is expressed in chitin‐forming tissues, testis and ovary, and accumulates in the cuticle. BmLSPMP‐like knockout, generated with CRISPR/Cas9, resulted in a stick‐like larval body shape phenotype. Over‐expression of BmLSPMP‐like in the sk mutant rescued its abnormal body shape. The results showed that BmLSPMP‐like may be involved in assemblage in the larval cuticle. CONCLUSION: Our results suggested that the dysfunction of BmLSPMP‐like may result in a stick body shape phenotype in silkworm, through the regulation of the arrangement of the chitinous laminae and cuticle thickness. Our study provides new evidence of the effects of LSPMP‐likes on lepidopteran body shape formation, metamorphosis and mortality, which could be an eco‐friendly target for lepidopteran pest management. © 2022 Society of Chemical Industry. Abstract : Mutation of BmLSPMP‐like induces a stick body shape in silkworm. BmLSPMP‐like is an evolutionarily conserved gene that exhibits synteny in Lepidoptera and underwent purifying selection in Lepidoptera evolution.